Dither-free bias control technique at the null point of the MZM based on power monitoring - Qu, Jing; Yin, Feifei; Dai, Yitang; Xu, Kun (SPIE, 2021)
A dither-free bias controller, locking a Mach-Zehnder modulator (MZM) working at the null bias point, is proposed and experimentally demonstrated. In microwave photonics systems, the null bias point of the MZM enables double sideband with suppressed carrier (DSB-SC) modulation utilizing for many applications. The output optical power of the MZM is monitored to dynamically lock the bias point using the hill-climbing algorithm. The bias controller is a feedback circuit consisting of a monitor photodetector (PD), a gain-controlled trans-impedance amplifier (TIA), a digital-to-analog converter (ADC), an analog-to-digital converter (DAC), an operational amplifier, and a microcontroller unit (MCU). To improve the accuracy of data processing, an adaptive magnification factor of the detection signal is added to the algorithm. In the experiment, the drift degree of the bias point with and without the bias controller has been compared in 150 minutes. The stability of the proposed bias controller is verified by using a 10 GHz RF signal. With the proposed controller, the bias point of MZM is stabilized within ±1 degree, and the optical carrier suppression ratio reaches more than 25dB. No dither is introduced into the spectrum hence the realization of frequency multiplication with no spurs, which has a broad prospect in microwave photonics.